Effective Teaching Behaviors of Clinical Nursing Teachers: A Qualitative Meta-Synthesis - Zhang, Jian; Zhou, Fenhua; Jiang, Jinxia; Duan, Xia; Yang, Xin (Frontiers in Public Health, 2022)
Objectives To identify, appraise, and synthesize the available evidence exploring the effective teaching behaviors of clinical nursing teachers. Design The Joanna Briggs Institute (JBI) guidelines were followed, and a meta-synthesis was conducted. Review Methods Following databases were searched for relevant qualitative studies published in English and reporting primary data analysis, including experiences and perceptions of nursing students: PubMed, EBSCOhost, OVID, etc. Qualitative Assessment and Review Instrument were used to pool the qualitative research findings. Through the repeated reading of the original literature, the similar findings were combined and sorted into new categories, and then summarized into different synthesized themes. Results A total of nine articles were included. The review process produced 29 subcategories that were aggregated into seven categories. The categories generated three synthesized findings: good teaching literacy, solid professional competence, and harmonious faculty-student relationship. Conclusions The effective teaching behaviors of clinical nursing teachers are the driving force for the progress and growth of nursing students. In order to improve the effectiveness of clinical nursing teaching, nursing teachers should be fully aware of effective teaching behaviors for nursing students to master nursing theories and skills.